Respostas bioquímicas, físico-químicas e microbiológicas do maracujá-amarelo durante armazenamento em atmosfera modificada e em diferentes temperaturas - Rotili, Maria Cristina Copello (2012)
The passion fruit is a climacteric fruit and at the phase of the Post harvest suffers important physiological transformations resulting of its own metabolism of ripening and others oxidative stress. The storage conditions of the passion fruit establish determining factor for its conservation. The refrigeration and modified atmosphere have been widely used in fruits, and the yellow passion fruit appears very promising in the use of these techniques, due to high instability of its physical and physiological characteristics post harvest. Therefore, this study was conducted with the objective of to evaluate the biochemical, physicochemical and microbiological of the passion fruit during its storage in modified atmosphere and at different temperatures. The work was divided into two experiments: The first consisted of the evaluation of the effect of storage temperature, where the fruits were stored at 5 º and 24 ºC. And in the second experiment evaluated the effect of modified atmosphere during the storage of the fruits at 5 °C. In both experiments the evaluations occurred at intervals of 10 days for 40 days, being evaluated the antioxidant activity DPPH and TEAC, the content of total phenolic compounds, ß-carotene and ascorbic acid, and physical and microbiological quality of the fruits. In the second experiment were included assessments of total titratable acidity, total soluble solids and enzymatic activity for polyphenol oxidase and peroxidase. In both experiments, it was utilized a completely randomized delineation, with five repetitions. The results showed that the total phenolic compounds, β-carotene and antioxidant activity of passion fruit juice were not affected by storage temperature and the content of total phenolic compounds of the juice increased with storage time. The effects of high temperature during storage were more evident in the appearance of the fruit than at the nutritional quality of the juice. The antioxidant activity of the juice, expressed in kidnapping DPPH radical, decreased during the storage, independent of temperature. Under the conditions of storage at 5 ° C and normal atmosphere, the shelf-life of passion fruit was higher and lasted up to 20 days in good conditions of marketing. The use of modified atmosphere was not able to reduce the losses of antioxidant activity of passion fruit juice during its storage. Total phenolics compounds and ascorbic acid were not affected by the use of modified atmosphere. Up to 30 days of storage there was suppressive effect of the activity of pathogens similarly in the two atmospheres of storage, suggesting that this effect was more related to low temperature. At 40 days of storage the modified atmosphere was more effective in inhibiting the activity of pathogens. The modified atmosphere was effective in reducing fresh mass loss and wrinkling of the rind, evidencing the high sensitivity of the fruit changes involving the loss of water and the importance of the use of modified atmosphere in maintaining their physical quality. Total soluble solids and total titratable acidity decreased during the storage and the modified atmosphere did not affect these results. The use of modified atmosphere during the storage at 5° C provided great conditions for marketing the yellow passion fruit up to 20 days. This study revealed the existence of activities of the polyphenoloxidase and peroxidase enzymes in the yellow passion fruit rind, but they were not identified in the fruit juice